Lama glama con signología y lesiones compatibles con paratuberculosis causadas por Mycobacterium avium subespecie avium - Jorge, M.C. (2008)
Guanaco, vicuña, alpaca and llama (Lama glama) are also known as Sudamerican camelids (SC). In Argentina llama was considered non profitable wildlife specie but now it is considered a mean for surviving because their meat, wool, leather and skin is valuable. SC are susceptible hosts of mycobacterial infections. A presumptive diagnosis is based on clinical and necropsy findings and is confirmed with bacterial isolation, molecular identification and histopathology. The objective of this publication is to describe a clinical case with clinical and necropsy findings consistent with paratuberculosis and its laboratory diagnosis in a captive llama from a zoo garden in Olavarría, Buenos Aires province. During necropsy granulomatous lesions resembling paratuberculosis in jejunum, ileon and mesenteric lymph nodes were observed. In direct smears and histopathology acid fast bacilli in clusters were detected. Mycobacterium avium subespecie avium was confirmed with bacteriology and the specific probe IS1245 was detected by PCR, IS900 Mycobacterium avium subespecie paratuberculosis specific probe was not demonstrated. These allowed confirming the etiology of a granulomatous enteritis case in llamas caused by Mycobacterium avium subespecie avium with clinical signs and lesions resembling paratuberculosis.